Improvement of Learning Motivation and Learning Outcomes by Applying The Problem Based-Learning Method - Nurcholish Arifin Handoyono; Rabiman Rabiman; Panggih Pribadi; Sigit Purnomo (Universitas Sarjanawiyata Tamansiswa, 2019)
Â Abstracts. The objective of this research is to find: (1) increased learning motivation by applying the PBL method, and (2) increased learning outcomes by applying the PBL method. This research uses classroom action research with three cycles, each cycle consists of four phases: (1) planning; (2) action; (3) observe; and (4) reflecting. The research subjects were students of class XI TKR A totaling 26 students. Data collection techniques in research are: (2) self-assessment to measure student motivation; and (2) Tests to measure the learning outcomes. The data obtained is quantitative and processed into descriptive statistics. Data were analyzed descriptively. The research results are as follows: (1) learning motivation in the first cycle of 12.46 categorized as low, the second cycle of 14.72 categorized as high, and the third cycle of 16.76 categorized as very high, has increased by 2.26 from the first cycle to the second cycle and by 2.04 from the second cycle to the third cycle; and (2) learning outcomes in the first cycle of 75,38, the second cycle of 81,79), and the third cycle of 83.33, has increased by 6. 41 from the first cycle to the second cycle and by 1.54 of the second cycle to the third cycle.